PENGARUH IKLIM SEKOLAH TERHADAP HASIL BELAJAR SISWA KELAS VIII SMP ISLAM ASHABUL KAHFI PONTIANAK - Irma Vidiyani; Asrori Asrori; Purwanti Purwanti (Universitas Tanjungpura, 2020)
AbstractSchool climate influences the way we do things at school. For example, in obtaining good learning outcomes in class VIII Islamic Middle School Ashabul Kahfi Pontianak. In the school climate there are also teacher behaviors and student behavior, teacher behavior and student behavior affect student learning outcomes. If the teacher's behavior and student's behavior is not good it will affect student learning outcomes that are not good, and vice versa. Because student learning success is determined based on student participation in schools such as work on assignments from the teacher, and participation in examinations. The general problem in this study is